Improvements for the corporative clients of the customer services department of a telecommunication company - Brousset Chaman, Milagros (2011)
The current situation of the corporative customers’ complaints of the Customer Services Department of a telecommunication company has been evaluated in this research. Software Arena has been used to perform simulations to get solutions that will improve the management rates of the Customer Services Department. Three solutions were proposed. However after evaluating each of them, the one that considers having five full time executives at the Back Office Area, instead of eight part time executives was considered the best alternative to choose. Additionally, it is recommended to have forty three full time executives at the Front Office area. This decision considers diminishing the personnel of this area in two executives.